Principal Strategies for Implementing Merdeka Belajar through a Deep Learning Approach at SD Negeri 35 Talang Kelapa - Silvia Wulansari; Reva Maria Valianti; Muhammad Juliansyah Putra (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aimed to describe the principal's strategies in implementing Merdeka Belajar through a deep learning approach at SD Negeri 35 Talang Kelapa. A descriptive qualitative approach was employed involving one principal, one school supervisor, six teachers, and six students selected through purposive sampling. Data were collected through observations, semi-structured interviews, and document analysis. Data were analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. Data credibility was ensured through source and technique triangulation. The findings revealed that the principal implemented several strategies, including strengthening teacher competence, conducting academic supervision, optimizing school facilities, and fostering a collaborative school culture. The study also identified challenges related to teachers’ understanding of deep learning, limited facilities, and adaptation to educational reforms. These challenges were addressed through continuous mentoring, internal training, and collaborative professional development. This study contributes to educational leadership literature by providing an empirical description of principal strategies for implementing deep learning within the Merdeka Belajar policy in elementary schools.